Symbolism and Derivation of Kiumars and Houshang, Two Characters in Shahnameh - Mahmud Sadeghzadeh; Mohammad Reza Hosseini Moghadam (مجله مطالعات ایرانی, 2017)
Ferdowsi's Shahnameh is the document of our national and religious identity and analyzing its structural and conceptual dimensions and particularly studying it comparatively with other religious and mythological texts seems to be necessary in order to achieve greater understanding of its mysteries and to attain its moral and spiritual doctrines and messages in any era and for any generation. In this study, through analyzing Shahnameh and taking advantage of valid sources on Shahnameh, mythology and history, initially the main subjects and titles in the mythology section were studied, particularly three mythological characters ( Kiumars (Qmars) and Houshang), then symbolic and Gnostic interpretations were analyzed and compared etymologically, and finally conclusions were presented according to available evidences. Accordingly, each character and hero in Shahnameh demonstrated a manifestation of religious beliefs, moral characteristics and his Ahura and evil nature, and he was given an appropriate title.